Clinical Correlates of Functional Motor Disorders: An Italian Multicenter Study. Issue 8 (22nd September 2020) - Tinazzi, Michele; Morgante, Francesca; Marcuzzo, Enrico; Erro, Roberto; Barone, Paolo; Ceravolo, Roberto; Mazzucchi, Sonia; Pilotto, Andrea; Padovani, Alessandro; Romito, Luigi M.; Eleopra, Roberto; Zappia, Mario; et al.
ABSTRACT: Background: Functional motor disorders (FMDs) are abnormal movements that are significantly altered by distractive maneuvers and are incongruent with movement disorders seen in typical neurological diseases. Objective: The objectives of this article are to (1) describe the clinical manifestations of FMDs, including nonmotor symptoms and occurrence of other functional neurological disorders (FND); and (2) to report the frequency of isolated and combined FMDs and their relationship with demographic and clinical variables. Methods: For this multicenter, observational study, we enrolled consecutive outpatients with a definite diagnosis of FMDs attending 25 tertiary movement disorders centers in Italy. Each patient underwent a detailed clinical evaluation with a definition of the phenotype and number of FMDs (isolated, combined) and an assessment of associated neurological and psychiatric symptoms. Results: Of 410 FMDs (71% females; mean age, 47 ± 16.1 years) the most common phenotypes were weakness and tremor. People with FMDs had higher educational levels than the general population and frequent nonmotor symptoms, especially anxiety, fatigue, and pain. Almost half of the patients with FMDs had other FNDs, such as sensory symptoms, nonepileptic seizures, and visual symptoms. Patients with combined FMDs showed a higher burden of nonmotor symptoms and more frequent FNDs. Multivariate regression analysis showed that a diagnosis of combined FMDs was more likely to be delivered by a movement disorders neurologist. Also, FMD duration, pain, insomnia, diagnosis of somatoform disease, and treatment with antipsychotics were all significantly associated with combined FMDs. Conclusions: Our findings highlight the need for multidimensional assessments in patients with FMDs given the high frequency of nonmotor symptoms and other FNDs, especially in patients with combined FMDs.